Self-learning for face clustering. (July 2018) - Shi, Xiaoshuang; Guo, Zhenhua; Xing, Fuyong; Cai, Jinzheng; Yang, Lin
Highlights: A self-learning framework including image decorrelation and a self-paced learning process, for face clustering. Providing quantitative analysis on the Gaussian distribution of global and local whitening faces. A novel self-paced learning model for face clustering, inspired by the learning process of human. Abstract: In this paper, we simulate the learning way of human to propose a self-learning framework for face clustering. Specifically, we first perform a decorrelation operation on face images through patch-based two-dimensional reconstruction, which has a similar function to the retina. Then we group the semantically similar faces by using a novel self-paced learning model, which is inspired by three major observations: (i) The learning process of human gradually proceeds from easy to complex tasks; (ii) The prior knowledge of human might change with the increase of learned experience; (iii) More prior knowledge usually leads to better prediction accuracy. Experiments on benchmark face databases demonstrate the effectiveness and efficiency of the proposed framework.